2015
DOI: 10.4038/jas.v10i3.8069
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability and interrelationships among quantitative traits in rapeseed (Brassica napus l.) advanced lines

Abstract: Improvement of the new rapeseed (Brassica napus L.) cultivars requires efficient tools to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
6
5
0
Order By: Relevance
“…Number of siliquae/plant showed high heritability (93.16%) with high genetic advance in percent of mean (37.74%). Similar result was also found by Rameeh (2013) for this trait. Number of secondary branches/plant exhibited high heritability (75.69%) with very high genetic advance in percentage of mean (73.55%).…”
Section: Resultssupporting
confidence: 90%
“…Number of siliquae/plant showed high heritability (93.16%) with high genetic advance in percent of mean (37.74%). Similar result was also found by Rameeh (2013) for this trait. Number of secondary branches/plant exhibited high heritability (75.69%) with very high genetic advance in percentage of mean (73.55%).…”
Section: Resultssupporting
confidence: 90%
“…The predominant influence of environment on the number of pods per plant is demonstrated by the low value of heritability coefficient obtained on the basis of experiments. Similar results were presented by Ali et al (2003), Marinković et al (2003) and Sharafi et al (2015), whereas Sadat et al (2010), Zare and Sharafzadeh (2012) and Rameeh (2015) showed that the number of pods per plant is highly heritable. The lowest variability was observed for thousand seed weight.…”
Section: Discussionsupporting
confidence: 83%
“…Clustering analysis on the basis of yield and yield components can be used for a multidimensional evaluation of genotypes from different geographic origins or from advanced breeding lines and cultivars (Jankulovska et al 2014;Rameeh 2015). Such a clustering of genotypes enables them to be comprehensively assessed for practical use in plant breeding.…”
Section: Discussionmentioning
confidence: 99%
“…Nath et al, (2003) reported 5 clusters which support this result. Rameeh (2013) reported 4 clusters. Two dimensional scatter diagram was prepared by using principal component score I in X-axis and II in Y-axis.…”
Section: Cluster Analysismentioning
confidence: 99%